The Impacts of Public Administrative Quality on Profitable Enterprises in Vietnam - Bac Truong Cong; Doan Van Hoang (Journal La Sociale, 2021)
This study aims to understand the relationship between the quality of public administration and the rate of profitable enterprises by locality in Vietnam in the period 2015 - 2019. With a combined data set from two sources including The first is the Provincial Competitiveness Index (PCI) dataset jointly implemented by the Vietnam Chamber of Commerce and Industry (VCCI) with the support of the United States Agency for International Development (USAID) in Vietnam, the second is the "White Book of Vietnamese Enterprises" compiled and published annually by the General Statistics Office of Vietnam. Combined with panel data estimation method to assess the impact of public administration quality indicators on the rate of profitable enterprises by locality. Research results show that there exists a relationship between the quality of public administration and the rate of profitable enterprises. Especially the indicators of Entry Costs, Policy Bias, and Labor and Training have both positive and negative effects with very strong statistical significance.